2017
DOI: 10.1103/physreve.96.053106
|View full text |Cite
|
Sign up to set email alerts
|

Shock-wave-like structures induced by an exothermic neutralization reaction in miscible fluids

Abstract: We report shock-wave-like structures that are strikingly different from previously observed fingering instabilities, which occur in a two-layer system of miscible fluids reacting by a second-order reaction A+B→S in a vertical Hele-Shaw cell. While the traditional analysis expects the occurrence of a diffusion-controlled convection, we show both experimentally and theoretically that the exothermic neutralization reaction can also trigger a wave with a perfectly planar front and nearly discontinuous change in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…We have shown that the CDD effect can result in the development of a perfectly regular convective pattern [31]. The effect was found primarily for the pair HNO 3 /NaOH, but then it was demonstrated also for other systems, for example, HNO 3 /KOH, HCl/NaOH [32,33].…”
Section: Mathematical Formulationmentioning
confidence: 76%
See 4 more Smart Citations
“…We have shown that the CDD effect can result in the development of a perfectly regular convective pattern [31]. The effect was found primarily for the pair HNO 3 /NaOH, but then it was demonstrated also for other systems, for example, HNO 3 /KOH, HCl/NaOH [32,33].…”
Section: Mathematical Formulationmentioning
confidence: 76%
“…In the last years, this simple, irreversible chemical reaction occurring in liquid-liquid miscible systems was extensively studied, to mention but a few [28,29,[31][32][33]. The Rayleigh-Taylor plumes and fingers are commonly observed under gravity when the heavier A overlies the lighter B [28].…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 3 more Smart Citations